Double Confinement Hydrogel Network Enables Continuously Regenerative Solar‐to‐Hydrogen Conversion. (12th September 2022) - Qin, Haili; Li, Na; Xu, Hou‐Ming; Guo, Qiu‐Yan; Cong, Huai‐Ping; Yu, Shu‐Hong
Abstract: Soft matter catalyst system allowing controllable manipulation of the organized nanostructure and surface property holds the potential for renewable energy. Here we demonstrate the construction of a continuously regenerative hydrogel photocatalyst that confines the metal‐thiolate coordination induced nanocavity into robust micro‐sized spongy network for water splitting. Thanks to low vaporization enthalpy and fast proton mobility of water molecules confining in nanocavities, the composite delivers outstanding photocatalytic H2 production (TOF of 4568 H2  h −1 ), nearly 4.5 times higher than that on the catalyst without confinements. Incorporating with conductive polymers, the TOF is substantially improved to 7819 H2  h −1 . Impressively, continuous regeneration is for the first time achieved with H2 production retention improved from 24 % to 72 % by regulating optically‐active catalyst surfaces. This optical regeneration method provides new avenues for sustainable solar energy conversion. Abstract : A double‐confinement‐cavity engineering strategy is developed for fabrication of hydrogel photocatalyst toward water splitting. The size‐confinement effect as well as reversible metal coordination enable the resultant hydrogel network with excellent performance in the photocatalytic H2 production and NIR‐regenerable behavior.